794Bisphosphonate use and risk of ovarian cancer, a nested case-control study using national health data. (2nd September 2021) - Tuesley, Karen; Webb, Penelope; Protani, Melinda; Spilsbury, Katrina; Pearson, Sallie-Anne; Coory, Michael D; Donovan, Peter; Stewart, Louise M; Pandeya, Nirmala; Jordan, Susan
Abstract: Background: Epithelial ovarian cancer (EOC) is the eighth most common cancer in women, has a five-year survival of ∼45%, and very few established modifiable risk factors. Some evidence suggests that bisphosphonates could have chemopreventive benefits, but few epidemiological studies have investigated the association between bisphosphonate use and incidence of EOC. Methods: We conducted a nested case-control study using linked administrative data. We identified 9, 367 women over 50 years diagnosed with EOC (cases) from 2004 to 2013, and for each case identified five controls from the Australian Medicare Enrolment database matched by age, state, area of residence, and area-level socioeconomic disadvantage. We assessed the associations between bisphosphonate use using dispensed prescription data (ever use, duration and dose) and EOC (overall, by histotype), adjusting for comorbidities and MHT use. We conducted sensitivity analyses in women with complete ascertainment of dispensing claims and for residents of one Australian state that had linked with data linked to hospital procedures, including oophorectomy. Results: Our analyses show an inverse association between bisphosphonate use and risk of EOC overall (OR = 0.81, 95%CI:0.75-0.88), and for endometrioid (OR = 0.51, 95%CI:0.33-0.79) and serous (OR = 0.84, 95%CI:0.75-0.93) histotypes. There was some evidence that higher dose and duration were associated with a greater reduction in risk. Results from sensitivity analyses were not appreciably different. Conclusions: Bisphosphonate use was associated with lower risk of EOC, suggesting bisphosphonates may reduce risk of ovarian cancer development. Key messages: Bisphosphonates may protect against development of serous and endometrioid ovarian cancers.